Can Religion Protect Against Suicide?. Issue 1 (January 2017) - Norko, Michael A.; Freeman, David; Phillips, James; Hunter, William; Lewis, Richard; Viswanathan, Ramaswamy
Abstract : Abstract: The vast majority of the world's population is affiliated with a religious belief structure, and each of the major faith traditions (in its true form) is strongly opposed to suicide. Ample literature supports the protective effect of religious affiliation on suicide rates. Proposed mechanisms for this protective effect include enhanced social network and social integration, the degree of religious commitment, and the degree to which a particular religion disapproves of suicide. We review the sociological data for these effects and the general objections to suicide held by the faith traditions. We explore how clinicians may use such knowledge with individual patients, including routinely taking a religious/spiritual history. The clinician who is aware of the common themes among the faith traditions in opposition to suicide is better prepared to address religious/spiritual matters, as appropriate, in crisis situations. The clinician who understands the patient's belief system is also better prepared to request consultation with religious professionals when indicated.